Genetic analysis of basal stalk rot resistance introgressed from wild Helianthus petiolaris into cultivated sunflower (Helianthus annuus L.) using an advanced backcross population - Talukder, Zahirul I.; Underwood, William; Misar, Christopher G.; Li, Xuehui; Seiler, Gerald J.; Cai, Xiwen; Qi, Lili (Frontiers in Plant Science, 2023)
Sclerotinia sclerotiorum is a serious pathogen causing severe basal stalk rot (BSR) disease on cultivated sunflower (Helianthus annuus L.) that leads to significant yield losses due to insufficient resistance. The wild annual sunflower species H. petiolaris, commonly known as prairie sunflower is known for its resistance against this pathogen. Sunflower resistance to BSR is quantitative and determined by many genes with small effects on the resistance phenotype.. The objective of this study was to identify loci governing BSR resistance derived from H. petiolaris using a quantitative trait locus (QTL) mapping approach. BSR resistance among lines of an advanced backcross population (AB-QTL) with 174 lines developed from a cross of inbred line HA 89 with H. petiolaris PI 435843 was determined in the field during 2017-2019, and in the greenhouse in 2019. Highly significant differences (p<0.001) for BSR response among AB-QTL lines were observed disease incidence (DI) in all field seasons, as well as disease rating (DR) and area under the disease progress curve (AUDPC) in the greenhouse with a moderately high broad-sense heritability (H 2) of 0.61 for the tested resistance parameters. AB-QTL lines and the HA 89 parent were genotyped using genotyping-by-sequencing and a genetic linkage map was developed spanning 997.51 cM and using 1,150 SNP markers mapped on 17 sunflower chromosomes. A total of 14 QTL associated with BSR resistance were identified on nine chromosomes, each explaining a proportion of the phenotypic variation ranging from 3.5% to 28.1%. Of the 14 QTL, eight were detected for BSR resistance in the field and six were detected under greenhouse conditions. Alleles conferring increased BSR resistance were contributed by the H. petiolaris parent at 11 of the 14 QTL.